Carbon Price versus Subsidies to Reduce Greenhouse Gas Emissions1. Issue 3 (September 2014) - Freebairn, John
<x xml:space="preserve">Abstract</x> This paper describes the operation of a price and a subsidy to reduce greenhouse gas emissions (GHG), and it compares and contrasts efficiency, redistribution and transactions costs of the two options. An initial comparison assumes comprehensive bases and negligible transaction costs. Then, actual examples for Australia are assessed, namely the carbon tax of 2012–2014 and the proposed Direct Action plan under consideration for 2015. It is argued that the price intervention option will be more cost effective per unit of GHG reduction, that it will be simpler and easier to operate, and that as part of a budget package it can provide at least as good a net distribution outcome.